Myocardial Blood Flow during General Anesthesia with Xenon in Humans: A Positron Emission Tomography Study - Schaefer, Wolfgang; Meyer, Philipp T.; Rossaint, Rolf; Baumert, Jan H.; Coburn, Mark; Fries, Michael; Rex, Steffen (Anesthesiology (Philadelphia), 2011)
Xenon has only minimal hemodynamic side effects and induces pharmacologic preconditioning. Thus, the use of xenon could be an interesting option in patients at risk for perioperative myocardial ischemia. However, little is known about the effects of xenon anesthesia on myocardial blood flow (MBF) and coronary vascular resistance in humans. Myocardial blood flow was noninvasively quantified by H₂¹⁵O positron emission tomography in six healthy volunteers (age: 38 ± 8 yr). MBF was measured at baseline and during general anesthesia induced with propofol and maintained with xenon, 59 ± 0%. Absolute quantification of MBF was started after the calculated plasma concentration of propofol had decreased to less than 1.5 μg · ml⁻¹. Compared with baseline (MBFbaseline, 1.03 ± 0.09 ml · min⁻¹ · g⁻¹; mean ± SD), MBF was decreased insignificantly by xenon (MBFxenon, 0.80 ± 0.22 ml · min⁻¹ · g⁻¹; -21%, P = 0.11). Xenon decreased the rate-pressure product (RPP; heart rate × systolic arterial pressure), an indicator of cardiac work and myocardial oxygen consumption (-15%, P < 0.04). When correcting for the RPP, the decrease in MBF observed during xenon anesthesia was reduced to -9% (MBFcorr-xenon, 1.42 ± 0.28 ml · g⁻¹ · mmHg⁻¹ vs. MBFcorr-baseline, 1.60 ± 0.28 ml · g⁻¹ · mmHg⁻¹, P = 0.32). Xenon did not affect the dependency of MBF on the RPP. Coronary vascular resistance did not significantly change (+15 ± 23%, P = 0.18) during xenon anesthesia. In healthy subjects, xenon has only minimal effects on coronary flow dynamics. These effects are probably of indirect nature, reflecting the decrease in myocardial oxygen consumption induced by the effects of xenon anesthesia on cardiac work.